Educational services: market or education? - Titarenko, Larissa G. (Journal of the Belarusian State University. Sociology, 2019)
The article analyzes the process of modernization of the system of higher education of the Republic of Belarus. In the context of international integration and the growth of global competition, the national system of higher education of Belarus is trying to use new mechanisms and approaches in order to respond to global challenges and solve national strategic objectives. The commercialization of education has become a new approach introduced in the 1990s. Today, it includes both public and private educational institutions, turning them into business organizations that are focusing on servicing the clients’ requests, because the entire system of higher education depends on the level of the clients’ funding. The article shares the specifics of business organizations and the institutions of higher education, which have different basic orientations, culture, and missions. Mixing these two types of organizations leads to the transformation of the system of higher education into a market segment and deprives the educational sphere of the ability to fulfill the missions of producing scientific knowledge, educating the individual and socializing citizens.
Keywords: Belarus; national system of higher education; clients; commercialization; entrepreneurial university; market of educational services; university mission; academic culture; modernization potential of the country